A community intervention to reduce alcohol consumption and drunkenness among adolescents in Sweden: a quasi-experiment - Robert Svensson; Björn Johnson; Karl Kronkvist (BMC, 2021)
Abstract Background Several studies have examined the effect of community interventions on youth alcohol consumption, and the results have often been mixed. The aim of this study is to evaluate the effectiveness of a community intervention known as the Öckerö Method on adolescent alcohol consumption and perceived parental attitudes towards adolescent drinking. Method The study is based on a quasi-experimental design, using matched controls. Self-report studies were conducted among adolescents in grades 7-9 of compulsory education in four control and four intervention communities in the south of Sweden in 2016-2018. Baseline measures were collected in autumn 2016 before the intervention was implemented in the intervention communities. Outcomes were the adolescents' alcohol consumption, past-year drunkenness, past-month drunkenness and perceived parental attitudes towards alcohol. Results Estimating Difference-in-Difference models using Linear Probability Models, we found no empirical evidence that the intervention has any effect on adolescents' drinking habits, or on their perceptions of their parents' attitudes towards adolescent drinking. Conclusion This is the first evaluation of this method, and we found no evidence that the intervention had any effect on the level of either young people's alcohol consumption or their past-year or past-month drunkenness, nor on their parents' perceived attitudes toward adolescent drinking. A further improvement would be to employ a follow-up period that is longer than the three-year period employed in this study. Trial registration ISRCTN registry: Study ID: 51635778 , 31th March 2021 (Retrospectively registered).